All-optical control of lead halide perovskite microlasers - Zhang, Nan; Fan, Yubin; Wang, Kaiyang; Gu, Zhiyuan; Wang, Yuhan; Ge, Li; Xiao, Shumin; Song, Qinghai (Nature communications, 2019)
Lead halide perovskites based microlasers have recently shown their potential in nanophotonics. However, up to now, all of the perovskite microlasers are static and cannot be dynamically tuned in use. Herein, we demonstrate a robust mechanism to realize the all-optical control of perovskite microlasers. In lead halide perovskite microrods, deterministic mode switching takes place as the external excitation is increased: the onset of a new lasing mode switches off the initial one via a negative power slope, while the main laser characteristics are well kept. This mode switching is reversible with the excitation and has been explained via cross-gain saturation. The modal interaction induced mode switching does not rely on sophisticated cavity designs and is generic in a series of microlasers. The switching time is faster than 70 ps, extending perovskite microlasers to previously inaccessible areas, e.g., optical memory, flip-flop, and ultrafast switches etc. Lead halide perovskite lasers have great potential as microscale organic light sources, but dynamic tuning has yet to be achieved. Here, Zhang, Fan et al. investigate how nonlinear modal interactions enable ultrafast mode switching with crossgain saturation.